Decoupling market incumbency from organizational prehistory: Locating the real sources of competitive advantage in R&D for radical innovation - Lourdes Sosa, M. (Strategic Management Journal, 2013)
Abstract The creative destruction literature has argued that differences in R&D performance of incumbent vs. entrant firms can be explained through organizational change theories about established vs. de novo firms. A disconnect exists between these theories and the available empirical evidence because often the best performing firms are established firms as well. I propose to resolve this disconnect by distinguishing between market incumbency (presence in a market prior to a discontinuity) and organizational prehistory (organizational experience prior to a transition, whether between technologies or between markets). Doing so allows me to contrast incumbent vs. entrant and de alio vs. de novo studies, and to suggest more robust future research designs. I illustrate my proposition using qualitative data from the anticancer and AIDS‐treatment drug markets. Copyright © 2012 John Wiley & Sons, Ltd.